Comparison of Renal Responses Between Continuous Mycophenolate Mofetil and Conversion from Mycophenolate Mofetil to Enteric-Coated Mycophenolate Sodium in Lupus Nephritis. Issue 2 (9th March 2022) - Liao, Yu-Wan; Hung, Wei-Ting; Chen, Yi-Ming; Hsu, Chiann-Yi; Lin, Ching-Heng; Hsieh, Tsu-Yi; Chen, Hsin-Hua; Hsieh, Chia-Wei; Lin, Ching-Tsai; Lai, Kuo-Lung; Tang, Kuo-Tung; Tseng, Chih-Wei; et al.
Abstract : Background: Mycophenolate mofetil (MMF) is extensively used for induction and maintenance therapy in patients with lupus nephritis (LN). Enteric-coated mycophenolate sodium (EC-MPS) was developed to reduce the adverse gastrointestinal effects of MMF. However, the therapeutic efficacy of MMF and EC-MPS in LN remains unclear. This study aimed to examine the treatment effects of EC-MPS in LN patients with prior MMF exposure. Methods: In this medical records review study, we included 54 LN patients, of whom 34 converted from MMF to EC-MPS at equimolar doses in 2016–2018 (nonmedical switching group) and 20 received continuous MMF treatment. Patients achieving complete remission or partial remission before the conversion were categorized as responders, whereas those who had never achieved complete remission or partial remission were categorized as nonresponders. Results: Baseline proteinuria was higher in the nonmedical switching group. Although elevation in proteinuria was observed after nonmedical switching, the serum creatinine concentration and estimated glomerular filtration rate both improved. Responders in the nonmedical switching group had lower proteinuria and higher complement 3 levels. In the subgroup analysis, albeit the modest increase in daily urine protein, anti–double-stranded DNA antibody levels, estimated glomerular filtration rate, and complements 3 and 4 seemed comparable after conversion. Conclusion: Switching to EC-MPS demonstrated a similar short-term renal response to continuous MMF treatment in LN patients. Prospective randomized trials are required to verify our findings.